Customer Satisfaction with the Service Quality of the One-Stop Service Center in Luang Prabang Capital - bounchanpaseuth, bouahieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The purpose aim to study were: 1) examine the level of opinions toward the quality of one-stop public service delivery among service users in Luang Prabang City, and 2) investigate whether service users’ satisfaction affects the quality of one-stop public service delivery at the One-Stop Service Center in Luang Prabang City. This research employed a survey research design. The target population consisted of 384 service users at the government One-Stop Service Center in Luang Prabang Capital, Luang Prabang Province. Data were collected using a questionnaire, and the data were analyzed using SPSS Program to compute the mean, standard deviation, and to conduct multiple regression analysis. The results found that: 1) Overall, the level of opinions toward the quality of service delivery at the One-Stop Service Center in Luang Prabang City was at a moderate level, with 3.06 and a standard deviation of 0.37. When considering each aspect individually, it was found that the dimension with the highest mean score was assurance in service provision, with 3.11 and SD = 0.53. This was followed by service reliability with 3.08 and SD = 0.47, the accessibility of services for service users recorded 3.06 and SD = 0.33, meanwhile, responsiveness to service users’ needs with 3.04 and SD = 0.54, and service tangibility also showed with 3.04 and SD = 0.47, respectively. 2) Service users’ satisfaction had a significant effect on the quality of one-stop service delivery at the One-Stop Service Center in Luang Prabang City. This satisfaction comprised satisfaction with progressive service delivery, continuous service delivery, and adequate service delivery, it was found that the variables possessed predictive power and were able to explain the variation in satisfaction affecting the quality of service provision at the One-Stop Service Center in Luang Prabang City by 22.90% with a statistical significance level of 0.05.